Effect of Peace Interventions on Students’ Peacebuilding Attitudes at Secondary School Level - Sadia Shaukat; Kiran Shahzadi; Umme-Farwa; Samina Safdar (NUST Journal of International Peace and Stability, 2021)
It is the need of the hour to incorporate peace promotion as one of the significant features of the educational institutions in Pakistan. The present study explores the impact of a peace promotion intervention, with control and experimental groups, in order to understand if specific planned activities can significantly improve the peacebuilding attitudes of students. The study is experimental in nature, administering a pre-test and a post-test for both the control and experimental groups. Two equal samples (n=69) of 10th-grade (secondary school) students were selected — using a random sampling technique — for the control and experimental groups. The results of this study indicated that peace interventions — comprising games, hands-on activities, and dialogues — contributed significantly to improving the peace-building attitudes of the students in the experimental group. In addition, the female students of the experimental group exhibited a greater improvement in their peace building attitudes in the post-test phase as compared to their male counterparts. Furthermore, the study also reveals that the female students in the control group also depicted improvement in the post-test. This research presents implications for policymakers and educationists that need to be considered when introducing peace promotion activities into the (secondary) school curriculum. This article argues that practical activities — targeted to inculcate peaceful behavior in the students — can serve as important tools in establishing an environment of peace in society in general.